2021
DOI: 10.1530/joe-20-0076
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the onset of leptin effects on the regulation of energy balance

Abstract: Leptin is a hormone required for the regulation of body weight in adult animals. However, during postnatal period, leptin is mostly involved in developmental processes. Because the precise moment in which leptin starts to exert its metabolic effects is not well characterized, our objective was to identify the approximate onset of leptin effects on the regulation of energy balance. We observed that male Lepob/ob mice started to exhibit increased body fat mass from postnatal day 13 (P13), whereas in females the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…The hypothalamic leptin–melanocortin system is a key element in the regulation of hunger, satiety, and energy balance [ 35 ]. Thus, genetic mutations that cause the absence of leptin or the leptin receptor (LepR) produce metabolic changes that resemble those observed during an intense negative energy balance, including hunger and the suppression of physiological processes that expend energy [ 135 ]. Furthermore, genetic mutations could also alter the dynamics of the release of FSH and LH secretion from the pituitary gland [ 136 ].…”
Section: Hormonal Control In Obesitymentioning
confidence: 99%
“…The hypothalamic leptin–melanocortin system is a key element in the regulation of hunger, satiety, and energy balance [ 35 ]. Thus, genetic mutations that cause the absence of leptin or the leptin receptor (LepR) produce metabolic changes that resemble those observed during an intense negative energy balance, including hunger and the suppression of physiological processes that expend energy [ 135 ]. Furthermore, genetic mutations could also alter the dynamics of the release of FSH and LH secretion from the pituitary gland [ 136 ].…”
Section: Hormonal Control In Obesitymentioning
confidence: 99%
“…Leptin can regulate animal food intake (Campfield et al, 1995;Baicy et al, 2007;Fischer et al, 2016), and energy balance (Friedman 2019;Teixeira et al, 2021). Moreover, some studies have shown that leptin also plays an important role in thermoregulation (Luheshi et al, 1999;Fischer et al, 2016;Weiner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%